1999
DOI: 10.1046/j.1365-313x.1999.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin 2‐oxidation and the SLN gene of Pisum sativum

Abstract: Summary Two cDNAs encoding gibberellin 2‐oxidases were isolated from maturing pea seeds. The first, PsGA2ox1, was isolated by activity screening of a Lambda‐ZAP cDNA library excised into phagemid form and expressed in Escherichia coli. The second, PsGA2ox2, was obtained initially as a PCR product using degenerate primers designed according to conserved regions of plant 2‐oxoglutarate‐dependent dioxygenases. E. coli heterologous expression products of PsGA2ox1 and PsGA2ox2 converted GA1 to GA8, as shown by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 29 publications
4
108
0
3
Order By: Relevance
“…The pronounced effect of long1 on the length of the first two internodes is most similar to that of the constitutive GA-response double DELLA mutant la cry-s (Potts et al, 1985;Weston et al, 2008) and the GA-overproducing sln mutant, which has a mutation in the GA catabolism gene GA2ox1 (Reid et al, 1992;Lester et al, 1999) (Figures 1A and 1B). By contrast, the phyB mutant, although equivalently elongated over later internodes, has only a weak effect on elongation of early internodes (Figures 1A and (A), (B), and (E) Phenotypes of elongated mutant seedlings under glasshouse conditions.…”
Section: Shoot Phenotype Of the Long1 Mutantmentioning
confidence: 64%
See 1 more Smart Citation
“…The pronounced effect of long1 on the length of the first two internodes is most similar to that of the constitutive GA-response double DELLA mutant la cry-s (Potts et al, 1985;Weston et al, 2008) and the GA-overproducing sln mutant, which has a mutation in the GA catabolism gene GA2ox1 (Reid et al, 1992;Lester et al, 1999) (Figures 1A and 1B). By contrast, the phyB mutant, although equivalently elongated over later internodes, has only a weak effect on elongation of early internodes (Figures 1A and (A), (B), and (E) Phenotypes of elongated mutant seedlings under glasshouse conditions.…”
Section: Shoot Phenotype Of the Long1 Mutantmentioning
confidence: 64%
“…GA3ox genes catalyze the conversion of inactive GA 20 to the active form GA 1 , whereas the GA2ox genes convert GA 1 to the inactive product GA 8 ( Figure 5A). GA2ox1 but not GA2ox2 also has the ability to convert GA 20 to another inactive product GA 29 (Lester et al, 1999). Figure 5D shows that the clearest effect of light was seen for GA2ox2.…”
Section: Long1 Mediates the Rapid Effects Of Light On Ga Economymentioning
confidence: 97%
“…One approach that has been used to investigate the role of GAs in seed set is ectopic expression in transgenic Arabidopsis of a cDNA, isolated from Pisum sativum L. (garden pea), encoding a GA 2-oxidase. This 2-oxidase, PsGA2ox2 (also known as 2ox2), can convert the active GAs, GA 1 and GA 4 , into the irreversibly inactivated products, GA 8 and GA 34 , respectively (Lester et al 1999). In several independent 35S : 2ox2 lines seed development is abnormal and siliques contain seeds that have aborted at various stages after fertilisation (Singh et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a recently characterized class of GA-catabolizing enzymes, the GA 2-oxidases, are involved in the irreversible conversion of active GAs and their precursors to inactive forms and potentially can be used to reduce the endogenous levels of active GAs. cDNAs that encode 2-oxidases were isolated recently from runner bean, Arabidopsis, pea, and rice (MacMillan et al, 1997;Lester et al, 1999;Martin et al, 1999;Thomas et al, 1999;Sakamoto et al, 2001) and shown to perform oxidation reactions at carbon 2 of various biologically active and inactive GAs in vitro. In addition, several ESTs from lotus, Medicago , maize, soybean, and tomato, and sequences from the Arabidopsis and rice genome-sequencing projects, have been identified as putative GA 2-oxidases (Elliott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%